Peranan Manajemen Fungsional dalam Implementasi Strategi pada Pencapaian Kinerja Perusahaan Kayu Berskala Besar di Kota Palu - Mohammad Iqbal (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
The purpose of this research is to analyze the contribution of functional management in the implementation of firm strategy which consists of 1) production management, 2) marketing management, 3) financial management, 4) human resources management toward the achievement of firm performance approach both simultaneously and partially.The result of this research and hypothesis testing show that 1) simultaneously, functional management in the implementation of firm strategy gives positive contribution to performance achievement of manufacture firms, 2) Partially functional management consist of: 1) production management, 2) marketing management, 3) financial management, 4) human resources management in the implementation of firm strategy gives positive and significant contribution to performance achievement of manufacture firm based on the balanced scorecard approach.Keywords: Functional Management, Implementation Strategy, Balanced Scorecard, Performance